Evaluation of phenyl-propanedione on yellowing and chemical-mechanical properties of experimental dental resin-based materials (Journal of Applied Oral Science, 2016)
Objective To evaluate the influence of phenyl-propanedione on yellowing and chemical-mechanical properties of experimental resin-based materials photoactivated using different light curing units (LCUs). Material and Methods Experimental resin-based materials with the same organic matrix (60:40 wt% BisGMA:TEGDMA) were mechanically blended using a centrifugal mixing device. To this blend, different photoinitiator systems were added in equimolar concentrations with aliphatic amine doubled by wt%: 0.4 wt% CQ; 0.38 wt% PPD; or 0.2 wt% CQ and 0.19 wt% PPD. The degree of conversion (DC), flexural strength (FS), Young’s modulus (YM), Knoop hardness (KNH), crosslinking density (CLD), and yellowing (Y) were evaluated (n=10). All samples were light cured with the following LCUs: a halogen lamp (XL 2500), a monowave LED (Radii), or a polywave LED (Valo) with 16 J/cm2. The results were analysed by two-way ANOVA and Tukey’s test (α=0.05). Results No statistical differences were found between the different photoinitiator systems to KNH, CLS, FS, and YM properties (p≥0.05). PPD/CQ association showed the higher DC values compared with CQ and PPD isolated systems when photoactivated by a polywave LED (p≤0.05). Y values were highest for the CQ compared with the PPD systems (p≤0.05). Conclusion PPD isolated system promoted similar chemical and mechanical properties and less yellowing compared with the CQ isolated system, regardless of the LCU used.